Answer:
12
Explanation:
Use the first two equations to solve for a and b.
multiply the second equation all the way through by -2
(-2)(a + 2b) = (-2)(7)
-2a -4b = -14 Add this to the first equation.
-2a - 4b = -14
+ 2a + 3b = 17
-b = 3 Multiply both sides by -1
b = -3 Plug -3 back into either of the 2 original equations to find a
a + 2b = 7
a + 2(-3) = 7
a - 6 = 7 Add 6 to both sides
a = 13
Now that we know a = -3 and b = 13, we can plug that into the third equation:
![((3a + 5b))/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/1mzwelwskp3yyiby4j9zqugah4ej91nfzy.png)
![(3(13) + 5(-3))/(2))](https://img.qammunity.org/2023/formulas/mathematics/college/thw5j2l959yp3q1f43qroyocda3r20bdzq.png)
![(39 -15)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/erpfnak6ocjlhoeo37zl7zghpv500z50oo.png)
= 12